Causal Effects of Tax Revenue and Budget Implementation in Nigeria - Duyile, Igbasan Emmanuel; Esther, Igbekoyi Olusola; Oladeji, Oladutire Elijah (Research Parks Publishers, 2024)
This study examines the causal relationship between taxation and budget implementation in Nigeria from 2000 to 2022, addressing the persistent challenge of aligning tax revenues with fiscal policy outcomes. Despite Nigeria's reliance on tax revenue, its impact on budget execution remains unclear, creating a knowledge gap in fiscal management. The research aims to assess the Granger causality between company income tax (CIT), value-added tax (VAT), and budget implementation, measured by capital expenditure. Time series data from the CBN Statistical Bulletin and World Development Indicators were analyzed. The findings revealed no Granger causality between CIT and budget implementation, while a significant Granger causality exists between VAT and capital expenditure, indicating that VAT revenue influences budget execution. The study recommends improved fiscal and monetary policy coordination to ensure VAT revenues are effectively channeled toward capital expenditure, fostering economic development.